Novel integrations of molten salt cavity tubular solar central receiver with existing gas-fuelled conventional steam power plants. Issue 1 (2nd January 2016) - Jamel, Mahmood S.; Abd Rahman, A.; Shamsuddin, A.H.
Abstract : This paper introduces a new method to integrate the existing equipment of the AL-Hartha steam plant located in Basra, Iraq, using a molten salt cavity tubular solar central receiver (SCR). Cycle Tempo is used to simulate the existing natural gas-fuelled conventional steam power cycle with consideration of the heat and pressure losses. The heliostat field and the central receiver subsystems are coded using MATLAB. The model couples the heat balance with the temperature computation of the receiver walls for calculation and analysis of the thermal losses. The proposed modified codes are capable of calculating heat losses, evaluating the integrated power plant and satisfying a wide range of SCRs. The results are verified against plant data and previous works in the literature and good agreement is obtained. The results show the potential of using a molten salt cavity tubular for low-range temperature to integrate the economizer (EN) and air preheater, as well as the optimum scheme for the integration of the existing plant with an SCR. It is observed that the best improvement for the existing AL-Hartha steam plant and the integrated molten salt cavity tubular SCR can be achieved by integrating EN, and there is about 9.1% saving in gas fuel consumption.